Associations between the sense of accessibility, accessibility to specific destinations, and personal factors: A cross-sectional study in Sendai, Japan - Ryo Tanimoto; Tomoya Hanibuchi (Transportation Research Interdisciplinary Perspectives, 2021)
Good urban and transport policymaking requires understanding both calculated/perceived accessibility to specific destinations and sense of accessibility (residents’ overall feelings of (in)convenience in their daily lives). This study investigated the correlations between personal factors, calculated accessibility (actual distances and travel time), perceived accessibility (residents’ perceived possibility of accessing specific destinations), and sense of accessibility. We conducted an online survey involving residents in the Sendai metropolitan area, Japan, from January 15 to February 9, 2021. The sample size was 1474. We considered previous studies and accessibility-related problems in Japan to determine what destinations and personal attributes the survey would enquire. The estimation results of ordinary regression models demonstrated that personal factors, including self-rated health, living in a central city, household composition, and transportation usage were associated with several measures of sense of accessibility. Good calculated accessibility to stations and food retailers was positively associated with the sense of accessibility without cars. Non-commuting and commuting longer than 30 min were positively associated with the sense of accessibility to what the respondents wanted. Perceived accessibility to important daily life destinations was positively associated with sense of accessibility. The neighborhood social cohesion was partly associated with the current sense of accessibility; however, this association was not observed under the assumption of not having access to a car. The results provide notable findings that connect existing accessibility measures and sense of accessibility in an Asian context.